Kimura disease with nephrotic syndrome in a child- A rare association - Anusree Majumder; Debraj Sen (Wolters Kluwer Medknow Publications, 2019)
Lymphadenopathy along with various systemic manifestations is commonly encountered in pediatric patients, tuberculosis being the commonest etiology. Occasional patients may present a diagnostic conundrum. Here, the authors report an unusual manifestation of Kimura disease (KD) presenting as nephrotic syndrome associated with mesenteric lymphadenitis in an 11-year-old male child. KD is a chronic inflammatory disorder of unknown etiology. It typically affects young adult males in the age range of 27-40 years and usually presents as painless itchy nodular masses in the head and neck region. The involvement of mesenteric lymph nodes along with a very young age of presentation makes it a rare case, posing a diagnostic challenge for the unsuspecting physician.